Estimating medium-term (40 years) carbon uptake in living biomass from Life Terra’s afforestation and reforestation actions: challenges and recommendations - Palmero-Barrachina, Jorge; Blazek, Petr; Sabaté, Santiago; Sauras-Yera, Teresa; Allasia-Grau, Samuel; Nadal-Sala, Daniel; Kallen, Sven; de Santana, Tiago; Cienciala, Emil (Frontiers in Forests and Global Change, 2025)
This study presents a comprehensive methodology for estimating potential biomass and carbon accumulation in European afforestation activities expected over a 40-year timespan, developed for the Life Terra project (LIFE19 CCM/NL/001200). We synthesized data from allometric equations, Yield tables, National Forest Inventories, and National Greenhouse Gas Inventory Reports across four European biogeographic regions: Alpine, Atlantic, Continental, and Mediterranean. While Life Terra encompasses six planting categories (ecological restoration, timber plantations, agroforestry/food forests, gardens, green infrastructure, and others), our analysis focused primarily on timber plantations due to data availability and reliability constraints. The study showed significant regional variations in planting density and growth patterns. Initial planting densities in timber plantations varied substantially across biogeographic regions (1,869–7,702 trees/ha), following exponential decline patterns over time. By year 40, individual tree biomass estimates ranged from 0.08 to 0.20 t/tree across regions and species types (conifers and broadleaves), with survival rates varying between 22.0 and 49.7%. This translated to stand-level biomass estimates of 54.7–232.6 t/ha at age 40 years. Our biomass estimates generally aligned with country-specific literature and IPCC default values, though showing considerable variation across sites, highlighting the importance of local conditions in tree growth and stand dynamics. The study provides a robust framework for assessing carbon sequestration potential in European afforestation projects, while acknowledging key uncertainties related to survival/mortality rates and climate change impacts. This methodology remains open to refinement through additional biomass equations and revised Yield tables. The future field validation studies should also include non-timber plantation categories that are not covered here.